2019
DOI: 10.1186/s12936-019-2683-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 24-h mobile reporting tool during a malaria outbreak in Mpumalanga Province, South Africa

Abstract: Background As surveillance is a key strategy for malaria elimination in South Africa, ensuring strong surveillance systems is a National Department of Health priority. Historically, real time tracking of case trends and reporting within 24 h—a requirement in South Africa’s National surveillance guidelines—has not been possible. To enhance surveillance and response efficiency, a mobile surveillance tool, MalariaConnect, was developed using Unstructured Supplementary Service Data (USSD) technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The penjawi or pustu collects data every week at the health centers. Every Similar results in a study in the Solomon Islands found that lack of training and refresher [16][17][18] , high workload and lack of professional staff could lead to reporting delays 19 . Research in Uganda found an increase in the achievement of indicators for completeness of reports by training malaria officers 20 .…”
Section: Processsupporting
confidence: 59%
“…The penjawi or pustu collects data every week at the health centers. Every Similar results in a study in the Solomon Islands found that lack of training and refresher [16][17][18] , high workload and lack of professional staff could lead to reporting delays 19 . Research in Uganda found an increase in the achievement of indicators for completeness of reports by training malaria officers 20 .…”
Section: Processsupporting
confidence: 59%
“…Population level epidemiological monitoring was improved in all four studies evaluating mHealth data collection tools in the setting of disease outbreaks, such as EVD or malaria. When compared to the standard paper method, there was improved timeliness of submission and data completeness [ 17 , 18 , 21 , 22 ]. Two observational studies found short messaging service (SMS) an effective means to obtain individual level symptom and health seeking data [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this trial, case investigations were frequently delayed when cases were more numerous, consistent with previous findings in South Africa. 20 Case reporting using mobile phones 56 , 42 has since been implemented and has helped improve response times. Sufficient standby capacity of case investigation teams in a targeted IRS strategy will be essential to ensure that health services are prepared for unexpected surges in cases.…”
Section: Discussionmentioning
confidence: 99%